PERAMALAN STOK SPAREPART MOBIL MENGGUNAKAN SINGLE EXPONENTIAL SMOOTHING - Widianto, Fransiskus Geofanny (JATISI, 2024)
Delindo Reswara is a spare part shop that recently made a change from having a manual system to a digital system, in order to progress smoothly into the digital realm, CV. Delindo Reswara needed a forecasting solution towards their spare parts stocks, so it could help them do a pre-order on their stock’s spare parts. Therefore, the methods that’s been carried out is to forecast and test its forecasting ability. The Single Exponential Smoothing as their forecasting method is done using a comparison towards its error percentage between two smoothing components value, that is α = 0.2 and α = 0.6, Testing using MAD, MSE, MAPE, and moving range chart as a decider for validity of the forecast method. It resulted in α = 0.6 having a lower error percentage with error value of MAD = 11.16, MSE = 171.07, MAPE = 0.26 and its forecasted data is in between of its upper and lower control limits all across the chart, so its safe to say that the forecasting method is valid to use.